The Conflict Arising from Street Vendors’ Resistance to Relocation and Its Impact on Evictions in the UIN SGD Bandung Campus Area - Kania Rahmadia Winata (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
The rejection of the relocation policy by street vendors (PKL) in the area surrounding UIN Bandung Campus led to social conflict and forced evictions, significantly affecting their socio-economic conditions. This study aims to analyze the dynamics of the vendors' resistance, including the underlying causes, the forms of conflict that emerged, and the socio-economic impacts of the forced evictions. A qualitative research approach was employed using participant observation, in-depth interviews, and field documentation conducted over a five-day period. The findings reveal that the relocation policy was implemented without meaningful participation from the street vendors, resulting in tensions and a lack of voluntary acceptance of the decision. The new relocation site, which was considered less strategically located, led to declining incomes and increased psychological distress among the vendors. The study concludes that the absence of participatory dialogue and inclusive decision-making was the primary cause of the relocation conflict and the resulting social injustice. This research contributes to the literature by emphasizing the importance of dialogue-based and participatory policymaking, particularly in the governance of public spaces within higher education environments, an area that has often received limited attention in government policy.